2011
DOI: 10.1039/c0cp02684k
|View full text |Cite
|
Sign up to set email alerts
|

Structural organization and phase behaviour of 1-butyl-3-methylimidazolium hexafluorophosphate: an high pressure Raman spectroscopy study

Abstract: The complexity of the phase diagram of a representative room temperature ionic liquid (1-butyl-3-methylimidazolium hexafluorophosphate, [bmim][PF 6 ]) is explored by means of Raman spectroscopy at high pressure (up to 1000 MPa) and high temperature (from room temperature to 100 1C) conditions. The first experimental evidence of the existence of a second crystalline phase for this salt at high pressure conditions is provided. By comparing the low frequency vibrational bands for the liquid state and the two obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 39 publications
5
51
2
Order By: Relevance
“…e . enhancing denser packing and interactions with larger number of neighboring cations . We note that there was no higher wavenumber minor contribution observed in contrast to the results of Chaurasia et al .…”
Section: Resultscontrasting
confidence: 88%
See 2 more Smart Citations
“…e . enhancing denser packing and interactions with larger number of neighboring cations . We note that there was no higher wavenumber minor contribution observed in contrast to the results of Chaurasia et al .…”
Section: Resultscontrasting
confidence: 88%
“…Literature data suggest that the P―F symmetrical stretching vibration of PF 6 − anion is rather sensitive to changes in the symmetry of the microenvironment upon changing the polarity of the solvent used to dilute IL and to the structural pattern of H‐bonding interactions whose changes may be induced by applying high pressure to neat IL . In the mixtures of BmimBF 4 with water a slight blueshift in the Raman spectra of a similar symmetric B―F stretching of anion was observed upon dilution of the IL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown the potential significant effect that pressure has on probing the nature of microscopic structures of ionic liquids. 30 Su et al 31 and Russina et al 32 6 ] experienced a liquid-solid phase transition at about 0.5 GPa. Under high pressures, the relative weights of the intermolecular forces defining the aggregation state are altered, and the repulsive side of the intermolecular side of the intermolecular potential is explored.…”
Section: Introductionmentioning
confidence: 99%
“…With this purpose, aprotic ILs have been studied under high pressure for several years [15][16][17][18][19][20]. On the contrary, studies about the effect of high pressure on PILs started to appear in the literature only a few years ago [12][13][14]21].…”
Section: Introductionmentioning
confidence: 97%